1982
DOI: 10.1128/aac.22.2.346
|View full text |Cite
|
Sign up to set email alerts
|

Activities of amoxicillin and clavulanic acid combinations against urinary tract infections

Abstract: Urinary tract infections caused by P-lactamase-producing bacteria were treated with 500 mg of amoxicillin three times daily plus either 250 or 125 mg of clavulanic acid three times daily. The overall cure rate was 63.6%, 77.7% with the high dose of clavulanic acid and 53.8% with the low dose. Gastrointestinal intolerance was common in the high-dose clavulanic acid regimen.Formulations of amoxicillin with potassium clavulanate possess activity against many plasmid-mediated P-lactamase-producing bacteria (3, 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Although more relapses at 6 weeks were seen in the cephalexin group, this difference was not statistically significant. The bacteriological cure rates were similar to those previously reported (1,3,4,6). When the treatment failed, this was not due to emergence of resistance to either drug.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although more relapses at 6 weeks were seen in the cephalexin group, this difference was not statistically significant. The bacteriological cure rates were similar to those previously reported (1,3,4,6). When the treatment failed, this was not due to emergence of resistance to either drug.…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown in vitro that this agent will render an ampicillin-resistant organism susceptible to ampicillin if resistance is due to production of a P-lactamase which is inhibited by clavulanic acid (1,5,10,12). This in vitro effect has been confirmed in vivo in several trials of a combination of amoxicillin with clavulanic acid in the treatment of urinary tract infections (1,3,4,6 Growth from this specimen was regarded as significant if it yielded more than 105 CFU/ml of a single species. Significant pyuria was defined as -20 pus cells per ,ul.…”
mentioning
confidence: 76%
“…Two clinical trials found that the frequency of gastrointestinal events is related to the dosage of clavulanic acid. 30,31 Moreover, the higher incidence of amoxicillin/clavulanic acid-induced diarrhoea could be explained by its greater resistance to b-lactamases, which may result in a higher concentration of amoxicillin in the intestine and a consequent stronger modification of the bacterial flora. In addition, a double-blind cross-over study demonstrated that amoxicillin/clavulanic acid is often associated with small intestinal motor disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have demonstrated that amoxicillin plus the beta-lactamase inhibitor clavulanic acid (A-C) is effective in urinary tract infections due largely to amoxicillin-resistant bacteria (1,3,5,8). The cure rate for infections due to amoxicillin-resistant bacteria is similar to that caused by amoxicillin-susceptible organisms, and the addition of low doses of clavulanic acid to amoxicillin did not appear to increase the incidence of adverse reactions (7).…”
mentioning
confidence: 98%